A Comparison of Evans Blue and 4-(p-Iodophenyl)butyryl Albumin Binding Moieties on an Integrin αvβ6 Binding Peptide - Ryan A. Davis; Sven H. Hausner; Rebecca Harris; Julie L. Sutcliffe (Pharmaceutics, 2022)
Serum albumin binding moieties (ABMs) such as the Evans blue (EB) dye fragment and the 4-(p-iodophenyl)butyryl (IP) have been used to improve the pharmacokinetic profile of many radiopharmaceuticals. The goal of this work was to directly compare these two ABMs when conjugated to an integrin αvβ6 binding peptide (αvβ6-BP); a peptide that is currently being used for positron emission tomography (PET) imaging in patients with metastatic cancer. The ABM-modified αvβ6-BP peptides were synthesized with a 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetracetic acid (DOTA) chelator for radiolabeling with copper-64 to yield [64Cu]Cu DOTA-EB-αvβ6-BP ([64Cu]1) and [64Cu]Cu DOTA-IP-αvβ6-BP ([64Cu]2). Both peptides were evaluated in vitro for serum albumin binding, serum stability, and cell binding and internalization in the paired engineered melanoma cells DX3puroβ6 (αvβ6 +) and DX3puro (αvβ6 −), and pancreatic BxPC-3 (αvβ6 +) cells and in vivo in a BxPC-3 xenograft mouse model. Serum albumin binding for [64Cu]1 and [64Cu]2 was 53–63% and 42–44%, respectively, with good human serum stability (24 h: [64Cu]1 76%, [64Cu]2 90%). Selective αvβ6 cell binding was observed for both [64Cu]1 and [64Cu]2 (αvβ6 (+) cells: 30.3–55.8% and 48.5–60.2%, respectively, vs. αvβ6 (−) cells <3.1% for both). In vivo BxPC-3 tumor uptake for both peptides at 4 h was 5.29 ± 0.59 and 7.60 ± 0.43% ID/g ([64Cu]1 and [64Cu]2, respectively), and remained at 3.32 ± 0.46 and 4.91 ± 1.19% ID/g, respectively, at 72 h, representing a >3-fold improvement over the non-ABM parent peptide and thereby providing improved PET images. Comparing [64Cu]1 and [64Cu]2, the IP-ABM-αvβ6-BP [64Cu]2 displayed higher serum stability, higher tumor accumulation, and lower kidney and liver accumulation, resulting in better tumor-to-organ ratios for high contrast visualization of the αvβ6 (+) tumor by PET imaging.